The pleiotropic effects of levothyroxine replacement therapy in patients with subclinical hypothyroidism and hypertension - M.A. Orel; L.P. Martynyuk (Mìžnarodnij Endokrinologìčnij Žurnal, 2023)
Background. According to epidemiological studies, the prevalence of subclinical hypothyroidism is about 6 % and it depends on age, gender, region of residence and, at the same time, significantly exceeds the frequency of primary hypothyroidism. Within one year, 5 % of cases of subclinical hypothyroidism turn into the manifested form. Delayed diagnosis of the disease increases the risk of serious complications. It is still controversial whether subclinical hypothyroidism affects blood pressure because of conflicting results in published studies. Thus, the aim of this study was to assess the effects of levothyroxine replacement therapy in patients with subclinical hypothyroidism and hypertension on lipid metabolism, functional state of the endothelium and cognition. Materials and methods. Thirty-one patients with subclinical hypothyroidism and stage 2 hypertension participated in the study, among them 12 (38.71 %) men and 19 (61.29 %) women. The average age of participants was 63.19 ± 1.93 years. The study examined lipid profile, functional state of the endothelium, and cognitive functions based on the results of the Montreal Cognitive Assessment before and after 3 months of additional administration of the levothyroxine replacement therapy at a dose 25–50 µg daily. Results. The lipid analysis revealed a significant decrease in total cholesterol for 10.08 % (5.54 ± 0.17 mmol/L against 6.23 ± 0.25 mmol/L, Р < 0.05), low-density lipoprotein cholesterol for 24.5 % (3.39 ± 0.17 mmol/L against 4.49 ± 0.27 mmol/L, Р < 0.01), triglycerides for 19.42 % (1.66 ± 0.11 mmol/L against 2.06 ± 0.16 mmol/L, Р < 0.05) compared to those at baseline. At the same time, patients with subclinical hypothyroidism and hypertension showed a reliable decrease in atherogenic dyslipidemias, 64.52 against 74.19 %. We also observed a reliable improvement of the functional state of the endothelium: the mean value of the endothelium-dependent vasodilation of the brachial artery increased for 11 % (6.56 ± 0.10 % against 5.91 ± 0.05 %, Р < 0.001). The results of the neuropsychological testing showed a reliable improvement of the cognitive functions among examined patients: the average score on the Montreal Cognitive Assessment raised from 23.77 ± 0.60 at baseline to 26.65 ± 0.47 after three months of taking levothyroxine, Р < 0.001. Conclusions. Levothyroxine replacement therapy in patients with subclinical hypothyroidism and hypertension was followed by a normalization of lipid profile and a decrease in atherogenic dyslipidemias, an improvement of the functional state of the endothelium and state of cognition.